Web-based anti-doping education: A needs analysis for achievement sport athletes - Rika Sepriani; Bafirman; Mudjiran (UIR Press, 2023)
This research is motivated by the many outstanding sports athletes who do not understand doping. Increasing the understanding of high-achieving sports athletes about doping can be done through online anti-doping education. The purpose of this study was to assess the need for web-based anti-doping education in high-performance athletes. This research is a quantitative descriptive study that included 40 athletes from five sport branches: powerlifting (7 athletes), weightlifting (8 athletes), athletics (4 athletes), soccer (12 athletes), and sepak takraw (9 athletes). Purposive sampling was used as a sampling technique. The instruments used in this study included a doping knowledge test and a web-based educational accessibility questionnaire for athletes. The data were analyzed using a descriptive quantitative method in the form of percentages. There were 40 people who participated in this study, with 26 male and 14 female respondents. Based on the research result, of the 40 participating athletes, one person (3%) had high doping knowledge, eight people (20%) had sufficient doping knowledge, and thirty-one people (78%) had less doping knowledge. Meanwhile, the achievement rate for web-based education accessibility questionnaires for achievement sports athletes was 89.75%. As a result, it can be concluded that web-based anti-doping education is needed and can be carried out on achievement-sport athletes. For this reason, related parties can conduct anti-doping education for every athlete in sports so that athletes can understand doping and prevent the use of doping by athletes.